Transvaginal natural orifice endoscopic surgery for myomectomy: Can it be a conventional surgery? - Hou, Qiannan; Li, Xin; Huang, Lu; Xiong, Ying; Feng, Dan; Zhang, Qiang; Zeng, Xiaoyan; Yang, Yang; Liu, Tianjiao; Li, Yalan; Lin, Yonghong; He, Li (Frontiers in Surgery, 2022)
Introduction: As a new minimally invasive surgery, transvaginal natural orififice transluminal endoscopic surgery (v-NOTES) has been proved to be suitable for the treatment of a variety of gynecological benign diseases. However, compared with other minimally invasive surgeries that have been widely used, such as conventional multi-ports laparoscopy and transumbilical laparoendoscopic single-site surgery (LESS), their advantages and disadvantages and how to choose are still unknown. The purpose of our study is to compare the advantages and disadvantages of the three minimally invasive surgeries inmyomectomy, and to provide theoretical basis for the wider development of vNOTES surgery. Material and methods: This retrospective study included 282 patients at our hospital who underwent laparoscopic myomectomy from May 2021 to March 2022. Based on the surgical approach, patients were classified into multiport, transumbilical laparoendoscopic single-site surgery (LESS), and vNOTES groups. The patients’ demographic characteristics and follow-up data were collected during the perioperative period and at one month postoperatively. Results: Among the three procedures, vNOTES had the shortest anal exhaust time but also the highest postoperative infection rate. Multiple linear regression analysis showed that the operative time increased by 3.5 min for each 1 cm increase in myoma, and the intraoperative bleeding increased by approximately 12 mL. The average duration of single pores increased by 25 min compared to that of multiports, and the operative duration increased by 10.48 min for each degree of adhesion. Conclusions: For gynecologists who have mastered vNOTES, this procedure has the same efficacy and safety as the two existing minimally invasive surgeries in myomectomy, but it shows obvious advantages in postoperative recovery.